A Diachronic Corpus for Literary Style Analysis - Vogel, Carl; Klaussner, Carmen (My University, 2018)
This research presents a resource for diachronic style analysis in particular the analysis of literary authors over time. Temporal style analysis has received comparatively little attention over the past years in spite of the possibility of an author's style frequently changing over time, a property that is not only interesting in its own right, but which also has implications for synchronic analyses of style. The corpus contains 22 American literary authors from the mid 19th to early 20th century that wrote largely in parallel. After describing the resource, we show how the corpus can be used to detect changing features in literary style.
Proceedings of the Eleventh International Conference on Language Resources and Evaluation (LREC 2018)
Keywords: Diachronic literary corpus; Style analysis; Linear regression; Digital Humanities; Computational linguistics; authorship profiling; stylochronometry; stylometry